Isolation and characterization of a variant subgroup GII-a porcine epidemic diarrhea virus strain in China. (March 2020) - Yang, Dan; Su, Mingjun; Li, Chunqiu; Zhang, Bei; Qi, Shanshan; Sun, Dongbo; Yin, Baishuang
Abstract: Background: Highly virulent variants of porcine epidemic diarrhea virus (PEDV) have been closely associated with recent outbreaks of porcine epidemic diarrhea (PED) in China, which have resulted in severe economic losses to the pork industry. Methods: In the current study, the variant PEDV strain HM2017 was isolated and purified and a viral growth curve was constructed according to the median tissue culture infective dose (TCID50). HM2017 were amplify with RT-PCR and analyzed by phylogeny analysis. Animal pathogenicity experiment was carried to evaluate the HM2017 clinical assessment. Results: Genome-based phylogenetic analysis revealed that PEDV strain HM2017 was clustered into the variant subgroup GII-a that is currently circulating in pig populations in China. The highest median tissue culture infectious dose of strain HM2017 after 15 passages in Vero cells was 1.33 × 10 7 viral particles/mL. Strain HM2017 was highly virulent to suckling piglets, which exhibited clinical symptoms at 12 h post-infection (hpi) (i.e., weight loss at 12–84 hpi, increased body temperatures at 24–48 hpi, high viral loads in the jejunum and ileum, and 100% mortality by 84 hpi). Conclusion: The present study reports a variant subgroup GII-a PEDV HM2017 strain in China and characterize its pathogenicity. PEDV strain HM2017 of subgroup GII-a presents a promising vaccine candidate for the control of PED outbreaks in China. Highlights: A variant subgroup GII-a PEDV strain HM2017 was successfully isolated in China. PEDV strain HM2017 appeared to be highly virulent in suckling piglets. PEDV strain HM2017 was well adapted to Vero cells, as evidenced by the rapid growth.